Hubungan Paparan Asap Rokok Terhadap Kejadian Hipertensi Pada Wanita di Kauman Kabupaten Brebes - Dewi Sulistyoningrum; Nurizqi Salsa Ramdhani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Background: Smoking is still the biggest problem in the world and causes 5.4 million people to die every year. It is explained that the acute effects caused by smoking can increase heart rate and blood pressure by increasing levels of the hormones epinephrine and norepinephrine due to activation of the sympathetic nervous system. Hypertension is a non-communicable disease that is found in many people in Indonesia and around the world and is still the most important health problem throughout the world and over time this problem is increasing. Hypertension can be caused by an unhealthy lifestyle such as smoking. The aim of this study was to determine the relationship between exposure to cigarette smoke and the incidence of hypertension in women in Kauman, Brebes Regency. Method This research is a quantitative study with an observational analytical approach and uses a cross sectional study design. The population in this study were women of productive age 15-64 years who lived in Kauman Village with a total sample of 20 respondents taken using a purposive sampling technique with the inclusion criteria being women aged 36-65 years and having family members who smoked at home. Results: In this study, the results obtained from the Chi-Square test were p value 0.914, if p > 0.05 then there was no significant relationship between the number of active smokers in the family and the incidence of hypertension in women in Kauman, Brebes district. And the p value of 0.045 means that there is a significant relationship between the length of exposure to cigarette smoke and the incidence of hypertension in women in Kauman, Brebes Regency. Conclusion: There is no relationship between the number of active smokers in the family and the incidence of hypertension in women in Kauman Brebes Regency and there is a relationship between the length of exposure to cigarette smoke and the incidence of hypertension in women in Kauman Brebes Regency.